2021
DOI: 10.1016/j.heliyon.2021.e06965
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of caffeic acid phenethyl ester on cadmium-induced testicular injury: A crucial role of antioxidant enzymes in male mice infertility

Abstract: Infertility in men is referred to inability to achieve pregnancy in fertile females after at least one year of regular intercourse. The lack of oxygen in the environment may lead to an imbalance of testes production. Swiss mice were alienated into four groups 10 mice/each. This included one negative normal control group I. The induction of infertility was achieved with injection of cadmium chloride at dose 3 mg/kg body weight for four consecutive days for the rest groups. Group III received vehicle (saline) fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…Caffeic acid phenethyl ester is a natural bioactive compound of propolis extract that possesses antioxidant property, which has been regarded as a potential inhibitory agent of infertility ( 23 ). Here, we found that the addition of CAPE to the extender significantly improved sperm motility, plasma membrane integrity, and acrosomal integrity ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Caffeic acid phenethyl ester is a natural bioactive compound of propolis extract that possesses antioxidant property, which has been regarded as a potential inhibitory agent of infertility ( 23 ). Here, we found that the addition of CAPE to the extender significantly improved sperm motility, plasma membrane integrity, and acrosomal integrity ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Male infertility cases are on the rise, and oxidative stress is a major contributing factor. Systemic oxidative stress, which is exacerbated by smoking, excessive alcohol use, exposure to various toxins, severe respiratory problems, inflammatory processes or other numerous prolonged disorders, are undeniable factors in the decline of male fecundity (El-Refaei & Abdallah, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, GSH content was determined in brain tissue using the method of El-Refaei et al. [ 37 ]. In this assay, the Ellman's reagent is reduced by the –SH groups of GSH to produce a yellow-colored 2-nitro-5-mercaptobenzoic acid, where the intensity of the color can be measured at 412 nm via the spectrophotometer.…”
Section: Methodsmentioning
confidence: 99%